2011
DOI: 10.1016/j.nrl.2011.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Evolución de pacientes con esclerosis lateral amiotrófica atendidos en una unidad multidisciplinar

Abstract: The treatment in multidisciplinary units does not change the neurological progression of the disease, but increases the survival of ALS patients regardless of their initial onset, emphasising the use of multidisciplinary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…This constraint has the potential to present a limited perspective on the overall clinical management of ALS and related MNDs, for which a multi-disciplinary approach has been well-supported (e.g., [113,127]). More specifically, the occurrence and management recommendations targeting aspiration pneumonia were not extracted in our literature search, omitting a discussion regarding functional airway clearance, and the roles of assisted-cough strategies, manual insufflation/exsufflation, and non-invasive positive pressure ventilation (for examples, see Sancho et al (2004; 2007); Miller et al (2009); Britton et al (2014)).…”
Section: Discussionmentioning
confidence: 99%
“…This constraint has the potential to present a limited perspective on the overall clinical management of ALS and related MNDs, for which a multi-disciplinary approach has been well-supported (e.g., [113,127]). More specifically, the occurrence and management recommendations targeting aspiration pneumonia were not extracted in our literature search, omitting a discussion regarding functional airway clearance, and the roles of assisted-cough strategies, manual insufflation/exsufflation, and non-invasive positive pressure ventilation (for examples, see Sancho et al (2004; 2007); Miller et al (2009); Britton et al (2014)).…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary ALS clinics confer survival and quality-of-life benefits [4144] and may facilitate patient enrollment in trials. In future, telemedicine may allow immobile patients to participate in multidisciplinary clinics for care and research participation.…”
Section: Challenges In Als Clinical Trialsmentioning
confidence: 99%
“…Various studies have shown that a multidisciplinary approach to patients with ALS [6,7,[14][15][16][17][18][19] is associated with decreased hospital admissions and length of hospital stay and increased use of ventilator support, percutaneous endoscopic gastrostomy (PEG) and palliative referral. This retrospective study shows that in the SUS, multiprofessional care can improve survival in patients with ALS, even for patients with bulbar onset who have a worse prognosis [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studies with multidisciplinary units in the UK [24], Ireland [15] and Spain [18] have concluded that compared to ALS patients who were treated in neurology services, patients treated in multidisciplinary units have better survival, and patients whose symptoms began at the bulbar level especially benefited from multidisciplinary care. Nevertheless, the average one-year mortality rate is approximately 50% overall and 57% in bulbar cases [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation